2020
DOI: 10.31219/osf.io/xdeyh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Levels of Burnout Syndrome in Croatian Critical Care Nurses: A Cross-Sectional Study

Abstract: Background: Burnout syndrome occurs in people who work in jobs which involve frequent and intense contact with people, especially healthcare workers. High dependency departments such as critical care units are very stressful environments, and this can lead to a greater incidence of burnout, especially of emotional exhaustion and poor personal accomplishment. Nurses are the largest group of healthcare workers, and so it is reasonable to expect they would have a high prevalence of burnout.Subjects and methods: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…Regarding other risk factors, men were more at risk of DP. This finding has already been observed in other reports in the literature (Chuang et al, 2016;Friganović and Selič, 2020;Merlani et al, 2011). In contrast, there was no association between the level of training and the different dimensions of burnout.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding other risk factors, men were more at risk of DP. This finding has already been observed in other reports in the literature (Chuang et al, 2016;Friganović and Selič, 2020;Merlani et al, 2011). In contrast, there was no association between the level of training and the different dimensions of burnout.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the prevalence of risk of burnout (68%), this was higher in this study than in previous studies carried out in Belgium in a general nursing population that reported a prevalence ranging from 17% to 38% (Vandenbroeck et al, 2017;Van den Heede et al, 2019). Compared with other studies carried out only among ICU nurses, we also observed a higher prevalence in our study in comparison to others that reported prevalence rates ranging from 3% to 27% (Friganović and Selič, 2020;Vermeir et al, 2018;Woo et al, 2020). Overall, the other studies were not carried out during the COVID-19 pandemic, the context of the pandemic may, therefore, explain the higher prevalence, especially since Belgium has been strongly affected by the pandemic.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Research conducted among physicians in Croatia on a national level before the pandemic showed that 63% of all physicians experienced burnout, and 16% of physicians experienced all three forms of burnout ( 38 ). The research on the levels of burnout syndrome in critical care nurses in Croatia showed that 22.1% of nurses expressed a high level of emotional exhaustion, with a lower level of depersonalization (7.9%), and 34.5% had a low level of personal accomplishment ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research shows that Slovenian nurses experience a high level of stress which results in inefficiency, staff turnover, and sick leave, subsequently decreasing the quality of care and their work satisfaction (Dobnik et al, 2018). Additionally, research on Croatian critical care nurses showed a high level of emotional Corresponding author: Leona Cilar, University of Maribor,Faculty of Health Sciences,Nursing Department,Žitna ulica 15,Maribor,Slovenia;email: leona.cilar1@um.si exhaustion and depersonalization (Friganović & Selič, 2020). Quality nursing care gives nurses a feeling of satisfaction with their job, which is often closely related to professional quality of life (Wulandari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%